Possibilities and limitations of fluorescence in situ hybridization technique in retrospective detection of low dose radiation exposure in post-Chernobyl human cohorts - Maznyk, N.A.; Vinnikov, V.A. (Цитология и генетика, 2005)
Cytogenetic analysis using the fluorescence in situ hybridisation (FISH) technique was performed late time after the Chernobyl accident in groups of liquidators, evacuees from 30 km exclusive zone, residents of radioactively contaminated areas and control donors age-matched to exposed persons.